Halal Tourism Development Strategy in Indonesia - Husni Pasarela; Andri Soemitra; Zuhrinal M Nawawi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The tourism industry has several goals, including to meet the physical, spiritual and intellectual needs of every tourist with recreation and travel and can improve the community's economy in order to realize the welfare of the community. Development StrategyHalal tourism is an alternative for the tourism industry in Indonesia along with the development of halal tourism which is part of the global Islamic economy industry. The rapid development of tourism has given rise to a new trend of developing halal tourism. However, its development still faces several obstacles and becomes a challenge in various parts of Indonesia. This study aims to describe the obstacles and challenges in the development of halal tourism in Indonesia and propose strategies that can be used to overcome these obstacles and challenges. This study uses a qualitative descriptive approach for data collection and uses content analysis techniques. The results of the study show that the obstacles to the development of halal tourism are the unprepared human resources and the lack of in-depth understanding of stakeholders and the community regarding the concept of developing halal tourism, community participation, which lacks innovation in promotional programs and inadequate facilities. Meanwhile, the challenges are the absence of regulations regarding the development of halal tourism in Indonesia and the lack of halal certification from the Indonesian Ulema Council.